A Comparative Study of Islamic and Contemporary Laws for the Prevention of Corruption in Pakistan - Prof. Dr. Matloob Ahmad (Journal of Religion and Society, 2025)
The corruption is a major obstacle in the development and stability, strengthening as well as in the justice system of Pakistan. It weakens institutions, undermines public trust and sets progress in the economy back. This study offers a comparative study of Islamic and modern legal framework for the prevention of corruption in Pakistan in an attempt to determine the imperfections of the existing systems of corruption prevention and determine how Islamic principles could be added to modern legal handicaps in their efforts to the corruption more effectively. The first section of the paper outlines the various kinds of corruption in Pakistan, which includes bribery, embezzlement, use of power, and nepotism. Then it looks at the current contemporary anti-corruption laws (National Accountability Ordinance [NAO] 1999) and institutions of the National Accountability Bureau (NAB). Though the presence of these measures, they have been criticized for being selective in their accountability, for political influence and for lack of success. On the contrary, the Islamic legal system is the one that has provided a moral and legal basis that has its roots within the concept of accountability (muhasabah), justice (‘adl), trust (amanah), and fear of punishment by one’s Lord. It analyzes Qur’anic injunctions, Prophetic traditions (Hadith) and ‘classical’ Islamic jurisprudence (Fiqh) in relation to financial misconduct and corruption. It points out that Islamic law emphasizes both inner reform and social accountability. The analysis of comparative laws reveals that although modern laws provide structure and mechanisms to enforce, Islamic teachings are in a holistic and preventive approach covering the external and the internal dimensions of corruption. The concluding part suggests that incorporation of Islamic ethics with modern legal system can be fruitful in strengthening efforts for elimination of corruption in the society of Pakistan. Keywords: Corruption, Islamic Law, Anti-Corruption Laws, Pakistan, Accountability